PEMBINAAN TERHADAP ANAK DIDIK PEMASYARAKATAN SEBAGAI UPAYA PENCEGAHAN TERJADINYA PENGULANGAN TINDAK PIDANA (Studi pada Lembaga Pembinaan Khusus Anak Klas II Bandar Lampung) - Vinanda, Olivia Rizka; Rahmah, Nur; Wibowo, Irham (Universitas Khairun, 2023)
Children are basically the next generation of the nation who should ideally grow and develop naturally according to their age, and be under the care and protection of parents, society and the state. In reality, there are children who commit criminal acts, such as theft, sexual abuse and narcotics. Punishment of children who commit criminal acts is carried out by the Special Child Development Institute as an effort to prevent repetition of criminal acts. The problem in this research is: How is the guidance of correctional students as an effort to prevent the recurrence of criminal acts at the Class II Special Development Institution for Children in Bandar Lampung and why are there inhibiting factors in the guidance of correctional students as an effort to prevent the repetition of criminal acts at the Special Development Institution Class II children from Bandar Lampung? The problem approach used in this research is empirical juridical. The data type consists of primary data and secondary data. Data collection through literature studies and field studies. Data analysis was carried out qualitatively. The results of this research show: Guidance for correctional students as an effort to prevent repetition of criminal acts at LPKA Class II Bandar Lampung is carried out in the coaching stages, namely initial coaching, advanced coaching and final coaching. Types of coaching include personality coaching (fostering religious awareness and fostering national and state awareness, fostering legal awareness and fostering intellectual abilities) as well as fostering independence. Factors that hinder coaching consist of statutory factors, namely the absence of technical instructions regarding coaching for children. crime, law enforcement factors, namely the quantity of guidance for correctional students, facilities and facilities factors, namely the limited means and facilities needed to carry out guidance, community factors, namely the negative attitude of the community towards former criminal children who have been released and returned to public.Keywords: Guidance, Correctional Students, Repetition of Criminal Offenses